Analysis of the causes of low investment in the colombian market (2014)
This paper aims to present the analysis and critique of the main causes of underinvestment Colombians through the market, posing as main effects: the absence of culture, ridiculous knowledge of the workings of the market, constant mistrust founded by the crisis and fraud presented both at home and abroad and the lack of regulation and incentives from the national government to the small businesses and thirsty capital investors to develop projects that can be beneficial for economic and social growth country.